Kreativitas Pembuatan Batik Berbasis Kearifan Lokal sebagai Daya Tarik Pengunjung Desa Wisata Kertosari, Pasuruan - Widiyatmo Ekoputro; Mulyanto Nugroho; Hamaz Zazirah Zam Zam Fath; Azizah Adhelia Wulandari; Adinda Mufida (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2025)
This community service program focuses on empowering the local community of Kertosari Village, Purwosari District, Pasuruan Regency, through creative batik-making based on local wisdom. This activity aims to support the development of sustainable ecotourism and enhance the competitiveness of tourist destinations in the global era. Tourism, as defined in Indonesian Law No. 10 of 2009, includes activities aimed at recreation, self-development, and exploration of local attractions. Kertosari Village, recipient of the 2019 Indonesia Sustainable Tourism Award, has strong potential as an ecotourism village with unique natural and cultural assets. Through training and capacity-building, this program seeks to equip local residents with batik-making skills that can serve as cultural products for tourism promotion. Funded by Universitas 17 Agustus 1945 Surabaya and supported by community partners, this initiative includes training sessions, seminars, and publications in SINTA-accredited journals and digital platforms. The expected outcomes are increased community participation in tourism, enhanced creative skills, and economic empowerment. Ultimately, this program aims to strengthen the identity of Kertosari Village as a sustainable tourist destination, while preserving local cultural heritage through batik.